Prediction of the Efficacy of Antihistamines in Chronic Spontaneous Urticaria Based on Initial Suppression of the Histamine Induced Wheal (2016)
ABSTRACT: Background: Antihistamines are the first line of treatment for chronic spontaneous urticaria. However, there is no effective method to predict whether an antihistamine will have a beneficial clinical effect or not. Objective: To assess whether the change in histamine-induced wheal and flare measurements 24 hours after administration of antihistamine can predict the efficacy of treatment. Methods: We performed a multicenter, triple-blind, randomized study. Patients received a daily oral dose of cetirizine, fexofenadine, bilastine, desloratadine, or ebastine over 8 weeks. After 4 weeks, a higher dose of antihistamine was administered to patients who did not experience a clinical response. A histamine skin prick test was carried out at baseline and 24 hours after the first dose of antihistamine. Disease severity (Urticaria Activity Score [UAS]), response to the histamine skin prick test, and impact on the patient's quality of life (Dermatology Life Quality Index [DLQI]) were determined every 2 weeks. Results: The study population comprised 150 patients (30 per group) and 30 controls. Twenty-four hours after administration of antihistamine, inhibition of the histamine wheal by >75% was significantly associated with better UAS and DLQI scores. The safety and efficacy of the 5 antihistamines were similar. After updosing, rates of disease control (DLQI score <5) increased from 58.7% to 76.7%. Conclusions: Measurement of the histamine-induced wheal can predict which patients will have a strong clinical response to antihistamines but has limited utility for identifying nonresponders. The clinical significance of these data could be relevant in the search for new urticaria treatment regimens.